Role of IRRI in increasing production of rice in India - Meah, Nafees; Marthi, Vijaya Kumar (Indian Farming, 2018)
The International Rice Research Institute-India partnership has been an outstanding exercise in collaboration, which advances global rice science and development on one hand and India’s rice production on the other. Because of its symbiotic nature, this partnership has not only endured, but has been enriched over the past half century.